2013
DOI: 10.1186/gb-2013-14-9-r107
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing reveals fine scale diversification and reticulation history during speciation in Sus

Abstract: BackgroundElucidating the process of speciation requires an in-depth understanding of the evolutionary history of the species in question. Studies that rely upon a limited number of genetic loci do not always reveal actual evolutionary history, and often confuse inferences related to phylogeny and speciation. Whole-genome data, however, can overcome this issue by providing a nearly unbiased window into the patterns and processes of speciation. In order to reveal the complexity of the speciation process, we seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
281
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(317 citation statements)
references
References 54 publications
(94 reference statements)
30
281
6
Order By: Relevance
“…Previous research indicated that SMALT is appropriate for mapping paired end reads when the reference genome is distantly related to the sampled species (Frantz et al, 2013 ). Furthermore, preliminary analyses showed that this soft ware produces the best results compared to other mapping soft ware (Fig.…”
Section: Processing Sequencesmentioning
confidence: 99%
“…Previous research indicated that SMALT is appropriate for mapping paired end reads when the reference genome is distantly related to the sampled species (Frantz et al, 2013 ). Furthermore, preliminary analyses showed that this soft ware produces the best results compared to other mapping soft ware (Fig.…”
Section: Processing Sequencesmentioning
confidence: 99%
“…As we will discuss later, the spatial and temporal coexistence of these suid species involved frequent hybridization events . This circumstance complicates the reconstruction of the evolutionary history of the genus Sus and calls into question whether species such as Sus celebensis, which currently live in the wild but may have been domesticated in the past, could have contributed to the gene pool of Asian pigs (Albarella et al, 2006;Larson et al, 2011;Frantz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is a general consensus that the Eurasian wild boar (Sus scrofa) and other sister species, such as Sus celebensis (Celebes warty pig), Sus verrucosus (Java warty pig), Sus cebifrons (Visayan warty pig), Sus philippensis (Philippine warty pig) and Sus barbatus (Bornean bearded pig), emerged in Southeast Asia in the early Pliocene (Figure 1), approximately 5.3-3.5 Myr ago (Larson et al, 2007a(Larson et al, , 2011Frantz et al, 2013). As we will discuss later, the spatial and temporal coexistence of these suid species involved frequent hybridization events .…”
Section: Introductionmentioning
confidence: 99%
“…The significant D-statistics varied from 0.07 to 0.17, which is slightly higher compared to analyses on recent radiations, such as Darwin's Finches (0.004 -0.092; Lamichhaney et al, 2015) and butterflies of the genera Heliconius (0.04; Dasmahapatra et al, 2012) and Papilio (0.04; Zhang et al, 2013). These values do fall within the range of studies on other hybridizing species, such as pigs (0.11 -0.23; Frantz et al, 2013), bears (0.04 -0.46; Liu et al, 2014, Cahill et al, 2015 and Xiphophorus fish (0.03 -0.56; Cui et al, 2013). A significant D-statistic does not necessarily indicate introgression between the species from which the genomes are being compared.…”
Section: General Patterns Of Introgressionmentioning
confidence: 50%
“…Previous research indicated that SMALT is appropriate for mapping paired-end reads when the reference genome is distantly related to the sampled species (Frantz et al, 2013). Furthermore, preliminary analyses showed that this software produces the best results compared to other mapping software ( Figure S7.1).…”
Section: Processing Sequencesmentioning
confidence: 93%